Pengaruh Perbedaan Suhu Air Pada Sanitasi Kerabang Terhadap Persentase Daya Tetas Puyuh Cortunix Japonica - Lasya Triananda; Afif Lukmanul Hakim; Nayla Azzahra Kuswandi; Dikri Fahmi Julian; Muhammad Ikhsan Suharlan; Muhammad Dinar Radhiyya (Jurnal Ilmu Peternakan Indonesia, 2026)
Pre-incubation management of hatching eggs is an important factor affecting hatchability because eggshell cleanliness helps prevent microbial contamination. This study aimed to determine the effect of wet cleaning using different water temperatures on the hatchability and mortality of Japanese quail eggs (Coturnix coturnix japonica). The experiment was conducted in May 2026 at the Vocational School of IPB University Sukabumi using a Completely Randomized Design with three treatments and three replications involving 90 eggs. The treatments were P0 (no wet cleaning), P1 (water at 25–30°C), and P2 (water at 40–45°C). Data were analyzed using the Kruskal–Wallis test. The results showed that water temperature had no significant effect (p > 0.05) on hatchability or mortality. The highest hatchability was observed in P0 (91,67%), followed by P1 (86,90%) and P2 (85,56%). In conclusion, wet cleaning with either room-temperature or warm water did not significantly affect hatching performance and can be safely applied to reduce eggshell contamination.